2023
DOI: 10.3389/fmars.2023.1234059
|View full text |Cite
|
Sign up to set email alerts
|

First insights into the population characteristics and seasonal occurrence of the great hammerhead shark, Sphyrna mokarran (Rüppell, 1837) in the Western Tuamotu archipelago, French Polynesia

Tatiana Boube,
Claire-Sophie Azam,
Antonin Guilbert
et al.

Abstract: The occurrence and seasonality of the Critically Endangered great hammerhead shark, Sphyrna mokarran, is data deficient in the Central Pacific region. Using photo-identification and laser-photogrammetry, we describe the seasonal population of great hammerhead sharks in the Tiputa pass (Rangiroa atoll) and Tuheiava pass (Tikehau atoll) in the Tuamotu archipelago of French Polynesia. During the austral summer of 2020 and 2021, we recorded a female-biased aggregation of at least 55 individuals (54 females; 1 unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…However, using SNPs, large-scale movement has been shown in both sexes (Green et al 2022). Philopatric behaviours exhibited by S. mokarran over large spatial scales have previously been discussed in the literature, yet it is unclear if these instances relate to natal philopatry, mating opportunities or functional residency behaviours like feeding events (Chapman et al 2015;Guttridge et al 2017;Boube et al 2023).…”
Section: Indo-pacific Structuringmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using SNPs, large-scale movement has been shown in both sexes (Green et al 2022). Philopatric behaviours exhibited by S. mokarran over large spatial scales have previously been discussed in the literature, yet it is unclear if these instances relate to natal philopatry, mating opportunities or functional residency behaviours like feeding events (Chapman et al 2015;Guttridge et al 2017;Boube et al 2023).…”
Section: Indo-pacific Structuringmentioning
confidence: 99%
“…In the western North Atlantic Ocean off Florida and The Bahamas, Guttridge et al (2017) reported the first evidence of philopatric behaviour for S. mokarran, with observations for both sexes of large-scale migrations, seasonal residency and site fidelity. In addition, Boube et al (2023) reported sexual segregation, seasonal residency or long-term site fidelity for S. mokarran off French Polynesia, noting aggregations and the possibility of natal grounds nearby. Similarly, Queiroz et al (2016) found that when S. mokarran were not making long distance movements, they remained in localised preferential habitats.…”
Section: Introductionmentioning
confidence: 99%